FROM REGIONAL TO GLOBAL – THE RUSSIAN FEDERATION STRATEGIES AND PERSPECTIVES - Cătălina-Laura PAȘCU (Challenges of the Knowledge Society)
The 21st century has surprised, after 2001, metamorphoses of the Russian Federation, both internally but especially at the external level, from a strategic regional identity towards a desired global identity. Identity and identification of power for the Russian Federation became a target centered on the recovery of the state’s major power and to restore the greatness of power. In the global context of geopolitical transformations, we can identify a new regional approach versus globalization – as a response reaction, in which new centers of power, and the powers print its presence in a world that tends toward structural changes of multipolar system. Thus, a strategic identity in the multipolar context is what wants and the Russian Federation. The present article, it is focused to debate the new dimensions of international theory and practice and aims to analyze a few aspects of defining social – political and cultural identity, which allow us to point out the extent to which, both geopolitical and geostrategic policies, identify and mobilize the meanings of evolution on postSoviet Russia. In a context on the multidimensional system of international relations, the proposed research was aiming at the theoretical and methodological issues focused on an interdisciplinary approach, specific geopolitical analysis, combining the meanings of identity perspective historical, political, social, economic and cultural.